2002
DOI: 10.1111/j.1349-7006.2002.tb01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Inhibits Growth Factor‐induced in vitro Angiogenesis via the Modulation of Mitochondrial Function in Endothelial Cells

Abstract: Betulinic acid (BetA), a pentacyclic triterpene, is a selective apoptosis-inducing agent that works directly in mitochondria. Recent study has revealed that BetA inhibits in vitro enzymatic activity of aminopeptidase N (APN, EC 3.4.11.2), which is known to play an important role in angiogenesis, but the anti-angiogenic activity of BetA has not been reported yet. Data presented here show that BetA potently inhibited basic fibroblast growth factor (bFGF)-induced invasion and tube formation of bovine aortic endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…These processes lead to the release of mitochondrial apoptogenic factors, activation of caspases, and DNA fragmentation [5][6][7]. It was observed that betulinic acid inhibited the in vitro activity of aminopeptidase N [8], an endogenous angiogenic factor, but could not inhibit the enzyme in vivo even though it inhibits mitochondrial function in endothelial cells [9]. Betulinic acid, by an antioxidant mechanism tends to protect congenital melanocyte naevi cells from UV-C-induced DNA strand breakage independent of p53 and p21 [10].…”
Section: Introductionmentioning
confidence: 99%
“…These processes lead to the release of mitochondrial apoptogenic factors, activation of caspases, and DNA fragmentation [5][6][7]. It was observed that betulinic acid inhibited the in vitro activity of aminopeptidase N [8], an endogenous angiogenic factor, but could not inhibit the enzyme in vivo even though it inhibits mitochondrial function in endothelial cells [9]. Betulinic acid, by an antioxidant mechanism tends to protect congenital melanocyte naevi cells from UV-C-induced DNA strand breakage independent of p53 and p21 [10].…”
Section: Introductionmentioning
confidence: 99%
“…88 Betulinic acid has also been shown to protect congenital melanocyte naevi cells from UV-C-induced DNA strand breakage independent of p53 and p21. 89 It was speculated that betulinic acid may be acting through an antioxidant mechanism.…”
mentioning
confidence: 98%
“…Reporter assay experiments were repeated three times and transfections performed in duplicate regimens. Ursolic and betulinic acids not only exhibit cytotoxic effect against endothelial cells, but also inhibits tube-like structure formation of aortic endothelial cells (Kwon et al, 2002;Mukherjee et al, 2004). In the present study treatment of OVCAR 432 cells with UABC increased the Sub-G1 cell population to 72.3%.…”
Section: Discussionmentioning
confidence: 52%